Database Design for Mere Mortals: A Hands-On Guide to Relational Database Design - Hernandez, Michael J.; Foreword by Getz, Ken (Boston Addison-Wesley, 2003)
Sound design can save you hours of development time before you write a single line of code. Based on the author's years of experience teaching this material, Database Design for Mere Mortals is a straightforward, platform-independent tutorial on the basic principles of relational database design. Database design expert Michael J. Hernandez introduces the core concepts of design theory and method without the technical jargon. Database Design for Mere Mortals will provide any developer with a common-sense design methodology for developing databases that work. 0201694719B04062001
Includes Index and Appendix
Keywords: Database design